Which Dental Procedures Lead to Greater Distress During Children's Dental Treatment? A Cohort Study - Haline Cunha de Medeiros Maia; Bruna Lorena Pereira Moro; Carolina de Picoli Acosta; Raiza Dias Freitas; Mayume Amorim do Vale; Ana Carla Crispim; José Carlos P. Imparato; Daniela Prócida Raggio; Mariana Minatel Braga; Fausto Medeiros Mendes (Association of Support to Oral Health Research (APESB), 2024)
Objective: To assess children's self-reported distress during dental procedures and investigate risk factors. Material and Methods: A total of 163 children (3-10 years old) were included from a clinical trial on diagnostic strategies for evaluating restorations in primary teeth. Treatment plans were elaborated based on the clinical examination performed at the baseline of the study. Dentists performed 742 dental procedures, and an external evaluator collected children's self-reported distress through the Wong Backer Facial Scale (WBFS) and dentists' opinions about children's behavior during the treatment. Kruskal-Wallis Test was performed to compare the distress and the dentists' perception of the different dental procedures, and multilevel ordered logistic regression analysis was conducted to the evaluate association between explanatory variables and the outcomes. Results: More complex procedures caused more distress in children (p=0.017), with a 5.5 times higher risk than simple operative treatments. Similarly, dentists reported children's worse behavior (p<0.001). Older children (older than 7 years) reported less distress than younger children (OR 0.52; CI 0.30-0.87; p=0.014). Patients reported greater distress in the first consultations, reducing the chance of higher scores by 16% in the next interventions. Conclusion: Children experience higher levels of distress during their first treatment appointments. More complex operative procedures and the child's age below 7 years were risk factors associated with greater distress during dental treatment.